2020
DOI: 10.3390/ijerph17134780
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Attention in Elementary School Students through Fixation Focus Training Activity

Abstract: The attentional problems of school children are a crucial topic due to abundant information in this digital era. There are five attention dimensions for children: focused attention, sustained attention, selective attention, alternating attention, and divided attention. Focused training is a traditional method of improving attention ability. Subjects are required to focus on a fixed point for an extensive period without blinking and to perceive small objects as large. This study investigates which types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This study found that the use of economic token interventions was beneficial in improving sample concentration during intervention conditions. Short pupil concentration problems make it difficult for teachers while teaching and learning sessions are underway (Lai & Chang, 2020). Autism is a lifelong neurodevelopmental disorder that usually appears in early childhood and affects a person's social, communication, relationship, and self-regulation skills.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the use of economic token interventions was beneficial in improving sample concentration during intervention conditions. Short pupil concentration problems make it difficult for teachers while teaching and learning sessions are underway (Lai & Chang, 2020). Autism is a lifelong neurodevelopmental disorder that usually appears in early childhood and affects a person's social, communication, relationship, and self-regulation skills.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EEG neurofeedback training was applied to children with ADHD, and cognitive functions (sustained attention, verbal working memory, and response inhibition) were improved in the treatment group [28]. Lai and Chang used fixation focus training activity to improve the attention of elementary school students [32]. The experiment group underwent focus training, conducted once a week, for 12 weeks.…”
Section: Methods To Improve Attentionmentioning
confidence: 99%
“…There were significant differences in the total scale, focused attention, and selective attention. However, it takes 12 weeks [32] or more [28] to improve the attention of the subjects. From the experimental results, specific brainwaves of the subjects can be induced by ten-minute stimulation.…”
Section: Methods To Improve Attentionmentioning
confidence: 99%
“…Attention is classified according to Sohlberg, cited by Lai & Chang (2020) in five dimensions, sustained attention, selective attention, focused attention, alternating attention, and divided attention. For this review, selective attention and sustained attention have been considered, as they are the main dimensions addressed in the articles reviewed.…”
Section: Introductionmentioning
confidence: 99%